USM OFFERS THE BEST IN PHARMACY STUDIES - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 11 March 2016 – Hamza Mostafa, 26, who is doing his Master’s postgraduate studies in the School of Pharmaceutical Sciences at Universiti Sains Malaysia (USM), deemed his experience studying here as being truly meaningful for his future.